Impact of M&A Announcement Involving Portuguese Listed Firms with Digital Vocation - Bruno F. S. LOBO; Luís M. P. GOMES (Communications of International Proceedings, 2021)
Mergers and / or acquisitions (M&A) are important business operations that can help firms to diversify their businesses, to become stronger and also more competitive. Most of these operations take place in international markets and between large firms, these being the main objects of scientific research. The main objective of this paper is to investigate the impact of the M&A announcement on the stock price of the firms involved, namely in terms of abnormal returns. The empirical work analyzes 10 integration operations, which took place since 2000, involving Portuguese firms listed in the PSI-20 index with a digital vocation. Using the event study methodology, the results suggest that the M&A announcement causes an abnormal aggregate net gain for the stockholders of the firms involved jointly. This is justified primarily by the improved stock performance of the target firms. However, abnormal average returns tend to stabilize about two weeks after the announcement. The conclusions reached are useful for academics, participants in stock markets, and decision makers on business combination strategies.
Keywords: Mergers and Acquisitions; Events Study; Stock Price; Abnormal Returns.